Porous transmission layer with reinforced framework and preparation method of porous transmission layer
By adding a reinforcement layer between the porous titanium sheets to form a gradient porous transport layer, the problems of low porosity of the sintered titanium sheet and random pore structure of the titanium fiber felt are solved, and a porous transport layer with high strength and high porosity is realized, which is suitable for the high-voltage environment of PEM electrolytic cells.
Patent Information
- Application Number
- CN202411889750.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-14
AI Technical Summary
The porosity and thickness of existing sintered titanium sheets are small, resulting in poor performance in PEM electrolytic cells. The pore structure distribution of titanium fiber felt is random and cannot be adjusted, resulting in large contact surface resistance and fewer electrochemical reaction sites.
A gradient porous transport layer is adopted, including a porous transport layer body in a sandwich structure and a cyclic additional layer. By adding a reinforcement layer between the porous titanium sheets, the porosity and pore size are adjusted to improve the conductivity and mechanical strength of the transport layer.
The strength and porosity of the titanium sheet after wet forming-sintering are improved, and are suitable for high preload and high pressure environments, reducing ohmic resistance, improving mass transfer ability and electrochemical reaction sites.
Smart Images

Figure CN119615210A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of proton exchange membrane water electrolysis, in particular to a porous transmission layer with a reinforced skeleton and a preparation method thereof. Background Art
[0002] The development of the green hydrogen economy will be a key factor in national energy security and economic decarbonization. The current relatively mature solution is to use renewable energy to produce green hydrogen through water electrolysis. Due to the advantages of proton exchange membrane (PEM) water electrolysis such as high power density, compact structure, high purity of hydrogen production, and rapid response to changes in load, it is considered to be the most promising technical path for large-scale implementation of water electrolysis to produce hydrogen. Generally, a single PEM electrolyzer is generally assembled from components including a catalyst layer, a bipolar plate, a porous transport layer, a proton exchange membrane, a sealing gasket, a current collecting plate, etc. Among them, the porous transport layer, as one of the core components, has the functions of conductivity, mass transfer, and support. Therefore, the porous transport layer needs to have the characteristics of good conductivity, high porosity, and high mechanical strength.
[0003] Titanium-based materials are currently the most widely used materials in porous transport layers, usually titanium fiber felt and sintered titanium sheets. Titanium fiber felt is a non-woven material made of titanium fibers, which has the advantages of high temperature resistance, corrosion resistance, high strength, and high porosity, which is conducive to gas-liquid transfer in PEM electrolyzers. Sintered titanium sheet is a metal sheet pressed from titanium metal powder and sintered at high temperature. It has the advantages of low manufacturing cost, smooth surface, low contact resistance with the catalyst layer and bipolar plate, and good conductivity. At present, titanium fiber felt is more widely used than sintered titanium sheets, and the technology of sintered titanium sheets is developing slowly.
[0004] In addition, the catalyst layer and the bipolar plate contact the two sides of the porous transport layer respectively. The catalyst layer and the bipolar plate perform water electrolysis reaction and material transfer respectively, and the inconsistent functions of the two determine the different requirements for the contact interface on both sides of the porous transport layer. For the catalyst layer / porous transport layer interface, the smaller the surface porosity and pore size of the porous transport layer, the larger the contact area with the catalyst layer, which is more conducive to reducing the contact resistance and increasing the electrochemical reaction sites. At the same time, a certain porosity must be guaranteed to remove the generated gas. For the contact interface of the bipolar plate / porous transport layer, the surface porosity of the porous transport layer needs to be relatively large, which is conducive to the transfer of water, that is, the supply of reactants, but in order to avoid excessive interface contact resistance, the porosity should be within a certain range. Since the catalyst layer and the bipolar plate have different requirements for the pores of the contact surface with the porous transport layer, a porous transport layer with a pore gradient will be one of the best solutions.
[0005] The main reason why existing sintered titanium sheets are rarely used is that they have a low porosity and a large thickness after being pressed and sintered at high temperature. The thickness of commercial titanium sheets is generally more than 1 mm, which seriously affects material transport. As a porous transport layer, it has poor performance in PEM electrolyzers, so its application in PEM electrolyzers is limited. At the same time, titanium fiber felt also has certain disadvantages, namely, the surface pore structure is randomly distributed, the pores cannot be adjusted, the contact with the catalyst layer is a line contact, the contact surface resistance is large, and there are fewer electrochemical reaction sites at the three-phase interface.
[0006] The original sintered titanium sheet can be made into a thin green sheet and sintered by wet forming technology. At the same time, pore-forming agents can be added to form pores in this process to increase the porosity, and the pores can be adjusted by selecting the pore-forming agent. However, although the sintered titanium sheet formed by this method is thin, it has low strength and is easy to break, thereby piercing the membrane electrode and reducing the performance and stability of the electrolyzer. It cannot be stably used in the high preload and high-pressure environment of commercial PEM electrolyzers. If the strength and performance of the titanium-based porous transport layer prepared by wet forming-sintering can be improved, its application scenarios can be greatly broadened. Summary of the invention
[0007] The purpose of the present invention is to provide a porous transport layer with a reinforced skeleton and a preparation method thereof, in order to solve the technical problems that the surface pore structure of the titanium sheet prepared by sintering using the current wet forming technology is randomly distributed, the pores cannot be adjusted, the contact with the catalyst layer is a line contact, the contact surface resistance is large, the electrochemical reaction sites at the three-phase interface are small, the porosity is small, the thickness is thin, the strength is low, and it is easy to break.
[0008] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a gradient porous transmission layer, comprising a porous transmission layer body arranged in a sandwich structure, the porous transmission layer body consisting of a first porous titanium sheet 1 at the top, a second porous titanium sheet 3 at the bottom, and a reinforcing layer 2 arranged between the first porous titanium sheet 1 and the second porous titanium sheet 3; and also comprising at least one set of cyclic additional layers;
[0009] The circulation additional layer includes a first porous titanium sheet 1 and a reinforcement layer 2 attached to one side of the first porous titanium sheet 1, or the circulation additional layer includes a second porous titanium sheet 3 and a reinforcement layer 2 attached to one side of the second porous titanium sheet 3;
[0010] The cyclic additional layer is overlapped with the hole transport layer body on one side or on both sides;
[0011] The titanium sheet of the circulation additional layer and the reinforcement layer 2 can have the same porosity and pore size as the main body, or different; the first porous titanium sheet 1 and the second porous titanium sheet 3 are both provided with pores; the thickness of the first porous titanium sheet 1 is the same as or different from the thickness of the second porous titanium sheet 3; the thickness of the first porous titanium sheet 1 and the thickness of the second porous titanium sheet 3 are both 1-2000μm.
[0012] Furthermore, the reinforcement layer is titanium fiber felt, titanium mesh, tungsten mesh or nickel mesh.
[0013] Furthermore, the thickness of the reinforcement layer is 1-2000 μm, and the porosity is 10%-90%.
[0014] Furthermore, an assembly structure of a gradient porous transport layer is included, the assembly structure comprising a porous transport layer body, a flow field arranged on one side of the top surface of the porous transport layer body, and a flow field catalyst layer arranged on one side of the bottom surface of the porous transport layer body.
[0015] The present invention also provides a method for preparing the above-mentioned gradient porous transport layer. The method for preparing the porous transport layer body comprises the following steps:
[0016] Step 1: Add solid and solvent into the same container;
[0017] Step 2: Stir the mixture prepared in step 1 thoroughly by one or more of ball milling, homogenizer stirring or magnetic stirring for a stirring time of 0.1-72h;
[0018] Step 3: After the slurry in step 2 is stirred, a plasticizer is added and stirred continuously, wherein the plasticizer is one or more of an alcohol plasticizer and an ester plasticizer;
[0019] The alcohol plasticizer preferably includes one or more of polyethylene glycol, polyalkylene glycol and triethylene glycol; the ester plasticizer includes one or more of phthalate, diisodecyl phthalate and dipropylene glycol dibenzoate;
[0020] The phthalate preferably includes one or more of butyl benzyl phthalate, diethylhexyl phthalate, diisononyl phthalate and dimethyl phthalate;
[0021] Step 4: After the slurry is stirred in step 3, a degassing treatment is performed. The degassing method includes one or more of vacuum degassing, vibration degassing and stirring degassing to prevent bubbles generated by stirring from affecting subsequent processes;
[0022] Step 5: wet forming the deaerated slurry;
[0023] The basic steps of wet forming treatment are: use a coater to evenly coat the fully mixed and degassed slurry on the demoulding substrate, and dry it during the coating process;
[0024] Step 6: Drying the coated green sheet for 1-60 hours; and cutting the dried green sheet into the size required by the electrolytic cell;
[0025] Step 7: hot-pressing the two cut green sheets with pores made by different pore-forming agents and the titanium fiber felt, with the titanium fiber felt sandwiched between the green sheets;
[0026] Step 8: Degumming the green sheet after hot pressing to remove the residual binder, plasticizer and undried solvent in the green sheet. The degumming temperature is between 10-1000°C and the glue environment is vacuum and inert gas atmosphere.
[0027] Step nine: The debonded green sheet is sintered at a high temperature, the sintering temperature is between 400-1800°C, and the sintering environment is a vacuum and inert gas atmosphere.
[0028] Furthermore, the solid in step one includes titanium powder, a pore former and a binder.
[0029] Furthermore, the titanium powder is hydrogenated dehydrogenated titanium powder, the average particle size is 1-500 μm, and the solvent is one or more of anhydrous ethanol, methyl ethyl ketone, trichloroethylene and water.
[0030] Furthermore, the binder is one or more of polyvinyl butyral, polyvinyl alcohol and polycarbonate acrylate.
[0031] Furthermore, the pore former is a high molecular organic material and / or a high molecular carbohydrate.
[0032] Furthermore, the high molecular organic material may be polymethyl methacrylate and / or polystyrene.
[0033] Furthermore, the high molecular carbohydrate may be one or more of starch, sucrose and cellulose.
[0034] The beneficial effects of the present invention are embodied in:
[0035] 1. The porous transport layer of the present invention can be prepared by the existing mature wet forming process or wet forming combined with hot pressing forming technology; compared with the porous transport layer in the traditional PEM electrolyzer, the gradient porous transport layer with the reinforcement layer has the following advantages:
[0036] 2. The strength of the wet-molded and sintered titanium sheet is improved, making it better suited for the high preload and high-pressure environment of the PEM electrolyzer.
[0037] 3. The structure design of the gradient porous transmission layer provided by the present invention is reasonable, and can be a simple sandwich layer structure, or a sandwich layer structure and a cyclic enhancement layer alternately arranged. Specifically, the cyclic enhancement layer can be cyclically superimposed with the porous transmission layer body arranged in a sandwich structure, and can be arranged on one side or on both sides. The titanium sheet of the cyclic additional layer and the enhancement layer can have the same porosity and pore size as the body, or different. It can be adjusted and set according to actual needs.
[0038] 4. Ability to adjust pores, with the advantage of pore gradient, can improve the mass transfer capacity of the transport layer, and reduce ohmic resistance, thereby improving performance.
[0039] 5. On the basis of ensuring strength, the thickness is much lower than commercial titanium sheets, which can effectively reduce the volume of the PEM electrolyzer stack.
[0040] 6. The porous transmission layer body is arranged in a sandwich structure, and the thickness and pore density of the first porous titanium sheet at the top and the second porous titanium sheet at the bottom can be consistent or different, which greatly increases the flexibility and variability of the structure.
[0041] 7. The present invention needs to protect the porous transmission layer structure prepared by compounding the porous titanium sheet and the reinforcement layer, which is original in the field of PEM electrolyzers and effectively fills the technical gap.
[0042] 8. The preparation technology used is very mature and reliable, suitable for large-scale production, and can significantly improve the production efficiency of PEM electrolyzer parts. Therefore, the gradient porous transport layer with a reinforcement layer has a good application prospect in the commercialization of PEM electrolyzers, especially for large-scale production.
[0043] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by practicing the present invention. The main purpose and other advantages of the present invention can be realized and obtained by the schemes particularly pointed out in the description. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0045] Figure 1 is a schematic diagram of a gradient porous transport layer with a reinforcement layer;
[0046] Figure 2 Schematic diagram of the assembly of a gradient porous transport layer with a reinforcement layer;
[0047] Figure 3 Flow chart of the preparation of gradient porous transport layer with reinforcement layer;
[0048] Figure 4 It is a schematic diagram of wet forming process;
[0049] Figure 5 is a schematic diagram of Embodiment 4;
[0050] Figure 6 This is a physical diagram of Example 1;
[0051] Figure 7 is a comparison diagram of polarization curves of Examples 1-4 and Comparative Example 1;
[0052] Figure 8 It is a comparison diagram of high frequency impedance between Example 1 and Comparative Example 2.
[0053] Figure numerals: 1-first porous titanium sheet, 2-reinforcement layer, 3-second porous titanium sheet, 4-flow field, 5-catalyst layer, 6-heater, 7-polyester film, 8-titanium mesh, 9-coater, 10-slurry, 11-second porous titanium sheet, 12-third porous titanium sheet, 13-fourth porous titanium sheet. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is described in detail below through examples. The examples are merely exemplary and can only be used to explain and illustrate the technical solution of the present invention, but cannot be interpreted as limiting the technical solution of the present invention.
[0055] In view of the problems that the porous transport layer formed by powder pressing and sintering in the PEM electrolyzer has poor performance, the contact surface resistance between the titanium fiber felt and the catalyst layer 5 and the bipolar plate is large, and the strength of the titanium-based porous transport layer prepared by wet molding and sintering is too low, the present invention proposes a porous transport layer with a reinforcement layer 2. The porous transport layer has a large porosity and adjustable pores, and can provide gradient pores in the through-surface direction. At the same time, it has high strength and can be suitable for the high preload and high-pressure environment of the PEM electrolyzer.
[0056] See also Figure 1 and Figure 5 As shown, the gradient porous transport layer includes a porous transport layer body arranged in a sandwich structure, and the porous transport layer body is composed of a top first porous titanium sheet 1, a bottom second porous titanium sheet 3, and a reinforcement layer 2 arranged between the first porous titanium sheet 1 and the second porous titanium sheet 3. It also includes at least one set of cyclic additional layers.
[0057] The circulating additional layer is a first porous titanium sheet 1 and a reinforcing layer 2 bonded to one side of the first porous titanium sheet 1, or the circulating additional layer is a second porous titanium sheet 3 and a reinforcing layer 2 bonded to one side of the first porous titanium sheet 3. The additional layer is overlapped with the porous transmission layer body on one side or both sides. The titanium sheet of the circulating additional layer and the reinforcing layer 2 may have the same porosity and pore size as the body, or may be different.
[0058] Furthermore, pores are provided on the first porous titanium sheet 1 and the second porous titanium sheet 3. The thickness of the first porous titanium sheet 1 is the same as or different from the thickness of the second porous titanium sheet 3; the thickness of the first porous titanium sheet 1 and the thickness of the second porous titanium sheet 3 are both 1-2000 μm. The reinforcing layer 2 is titanium fiber felt, titanium mesh, tungsten mesh or nickel mesh.
[0059] Furthermore, the thickness of the reinforcement layer 2 is 1-2000 μm, and the porosity is 10%-90%.
[0060] See also Figure 2 , comprising an assembly structure of a gradient porous transport layer, the assembly structure comprising a porous transport layer body, a flow field 4 arranged on one side of the top surface of the porous transport layer body, and a flow field 4 catalyst layer 5 arranged on one side of the bottom surface of the porous transport layer body.
[0061] The above-mentioned method for preparing the gradient porous transport layer and the method for preparing the porous transport layer body include the following steps:
[0062] Step 1: Add titanium powder, pore-forming agent, binder and other solids and solvent into the same container;
[0063] Step 2: The mixture prepared in step 1 is fully stirred by one or more of ball milling, homogenizer stirring or magnetic stirring, and the stirring time is 0.1-72h;
[0064] Step 3: After the defoamed slurry 10 in step 2 is stirred, a plasticizer is added and stirred continuously, wherein the plasticizer is one or more of an alcohol plasticizer and an ester plasticizer;
[0065] The alcohol plasticizer preferably includes one or more of polyethylene glycol, polyalkylene glycol and triethylene glycol; the ester plasticizer includes one or more of phthalate, diisodecyl phthalate and dipropylene glycol dibenzoate;
[0066] The phthalate ester preferably includes one or more of butyl benzyl phthalate, diethylhexyl phthalate, diisononyl phthalate and dimethyl phthalate;
[0067] Step 4: After the slurry 10 in step 3 is stirred, a degassing treatment is performed, and the degassing method includes one or more of vacuum degassing, vibration degassing and stirring degassing to prevent bubbles generated by stirring from affecting subsequent processes;
[0068] Step 5: subjecting the deaerated slurry 10 to wet forming treatment;
[0069] The basic steps of wet forming treatment are: use a coater to evenly coat the fully mixed and degassed slurry on the demoulding substrate, and dry it during the coating process;
[0070] Step 6: Drying the coated green sheet for 1-60 hours; and cutting the dried green sheet into the size required by the electrolytic cell;
[0071] Step 7: hot-pressing the two cut green sheets with pores made of different pore-forming agents and the reinforcing layer 2, with the reinforcing layer 2 sandwiched between the green sheets;
[0072] Step 8: Degumming the green sheet after hot pressing to remove the residual binder, plasticizer and undried solvent in the green sheet. The degumming temperature is between 10-1000°C and the glue environment is vacuum and inert gas atmosphere.
[0073] Step nine: The debonded green sheet is sintered at a high temperature, the sintering temperature is between 400-1800°C, and the sintering environment is a vacuum and inert gas atmosphere.
[0074] Furthermore, the titanium powder is hydrogenated dehydrogenated titanium powder, the average particle size is 1-500 μm, the solvent is one or more of anhydrous ethanol, methyl ethyl ketone, trichloroethylene and water; the binder is one or more of polyvinyl butyral, polyvinyl alcohol and polycarbonate acrylate. The pore former is a high molecular organic material and / or a high molecular carbohydrate. The high molecular organic material can be polymethyl methacrylate and / or polystyrene. The high molecular carbohydrate can be starch and / or sucrose and / or cellulose.
[0075] Embodiment 1:
[0076] This embodiment is prepared by combining wet molding technology with hot pressing molding technology. The preparation process is mature and reliable. The main process is as follows: Figure 3 As shown, the steps are:
[0077] Step 1: Add titanium powder, pore former, binder and solvent to the same container. The titanium powder used in this example is hydrogenated dehydrogenated titanium powder with an average particle size of 1-500μm. The solvent is one or more of anhydrous ethanol, methyl ethyl ketone, trichloroethylene and water. The embodiment of the present invention uses anhydrous ethanol. The binder is one or more of polyvinyl butyral, polyvinyl alcohol and polycarbonate acrylate. The embodiment of the present invention uses polyvinyl butyral. The pore former is a polymer organic material, such as polymethyl methacrylate, polystyrene, and a polymer carbohydrate, such as starch, sucrose, cellulose. One or more of the selected pore formers have a diameter of 0.1-1000μm. This embodiment uses polymethyl methacrylate microspheres with different diameter ranges, 50-80μm and 10-40μm, as pore formers for the two porous transmission layers, respectively. The mass ratios of titanium powder, solvent and binder in the slurry 10 are: 40wt%-80wt%: 15wt%-40wt%: 0.5wt%-10wt%; the volume ratio of titanium powder and pore former in the slurry 10 is: 40vt%-99vt%: 40vt%-99vt%;
[0078] Step 2: The mixture prepared in step 1 is fully stirred, and the stirring method is one or more of ball milling, homogenizer stirring or magnetic stirring. The stirring method used in this embodiment is magnetic stirring, and the stirring time is 0.1-72h;
[0079] Step 3: After the slurry 10 in step 2 is stirred, a plasticizer is added and stirred continuously. The plasticizer is one or more of an alcohol plasticizer and an ester plasticizer; the alcohol plasticizer preferably includes one or more of polyethylene glycol, polyalkylene glycol and triethylene glycol; the ester plasticizer includes one or more of phthalates, diisodecyl phthalate and dipropylene glycol dibenzoate; the phthalates preferably include one or more of butyl benzyl phthalate, diethylhexyl phthalate, diisononyl phthalate and dimethyl phthalate. The plasticizer used in this example is polyethylene glycol, which accounts for 0.5wt%-10wt% of the slurry 10 by mass. In this embodiment, the polyethylene glycol accounts for 2.5wt% of the slurry 10 by mass. The stirring method is the same as magnetic stirring, and the stirring time is 0.1-72h;
[0080] Step 4: After the slurry 10 in step 3 is stirred, a degassing treatment is performed. The degassing method includes one or more of vacuum degassing, vibration degassing and stirring degassing to prevent bubbles generated by stirring from affecting subsequent processes. The degassing method used in this embodiment is vacuum degassing;
[0081] Step 5: The deaerated slurry 10 is subjected to wet forming treatment. Figure 4 As shown. The substrate is a film treated with a release agent, and is a substrate for cast molding. In this example, the substrate is a polyester film 7 treated with silicone oil. The degassed slurry 10 is poured on the polyester film 7, and is coated and the thickness is controlled by a coater 9 with a gap. The gap of the coater 9 is between 0.02-5mm, and the coater 9 moves at a uniform speed on the substrate. The coating method is single coating molding or multiple times, twice or more, coating molding. This example uses a single coating molding, and the raw embryo sheet after coating molding is heated by a heater 6 at the same time. The heating temperature is between 20-80°C. In this embodiment, two green embryo sheets using different pore-forming agents, specifically polymethyl methacrylate microspheres with a particle size of 50-80μm and 10-40μm, are prepared.
[0082] Step 6: Drying the coated green sheet for 1-60 hours; and cutting the dried green sheet into the size required by the electrolytic cell;
[0083] Step 7: hot-press the two cut green sheets and titanium fiber felt with different pore-forming agents, and sandwich the titanium fiber felt between the green sheets. The titanium fiber felt used in this example has a thickness of 100 μm and a porosity of 45%. The hot-pressing temperature is 20-1000° C., the pressure is 0.1-1000 bar, and the hot-pressing time is 0.1-800 min. In this example, the hot-pressing temperature is 125° C., the pressure is 70 bar, and the hot-pressing time is 5 min.
[0084] Step 8: Degumming the green sheet after hot pressing, the purpose is to remove the residual binder, plasticizer and undried solvent in the green sheet, the degumming temperature is between 10-1000° C., 400° C. is selected in this embodiment, the degumming time is 0.5-72.0h, and the degumming environment is vacuum and inert gas atmosphere;
[0085] Step 9: The green sheet after debonding is subjected to high temperature sintering. The sintering temperature is between 400-1800°C. In this embodiment, 1000°C is selected. The sintering time is 0.5-90.0h. The sintering environment is vacuum and inert gas atmosphere. In this embodiment, the sintering is carried out in vacuum pure argon atmosphere. Figure 6 shown.
[0086] Example 2 is the same as Example 1, except that: 1) the reinforcement layer 2 is a stretched titanium mesh with a thickness of 1-1000 μm and a porosity of 1-95%; 2) the stretched titanium mesh used in this example has a thickness of 50 μm and a porosity of 20%; and the same pore-forming agent is used for pore formation in the example, namely, polymethyl methacrylate microspheres with a particle size of 50-80 μm, namely Figure 1 1 and 3 use the same pore-forming agent to form pores.
[0087] Embodiment 3:
[0088] The wet molding technology is used to directly prepare the reinforcement layer 2, and the thickness of the reinforcement layer 2 is 1-1000 μm, and the porosity is 1-95%. In this example, the thickness of the reinforcement layer 2 is 60 μm, and the porosity is 62%. In addition, the same pore-forming agent as in Example 1 is used for pore-forming, that is, polymethyl methacrylate microspheres with a particle size of 50-80 μm, that is, Figure 1 1 and 3 of the above use the same pore-forming agent to form pores, and the main steps include:
[0089] Step 1: The slurry 10 is configured in exactly the same manner as Steps 1 to 4 of Example 1;
[0090] Step 2: Place the tungsten mesh on a thickness-controlled template with holes. In this example, the template is a polytetrafluoroethylene membrane with a hole size of 40×40 mm. Figure 4 The polyester film 7 is placed on the hole, and then the tungsten mesh is placed on the hole, and then the coating is directly performed using the applicator 9;
[0091] Step 3: The drying and sintering steps are exactly the same as those in Example 1.
[0092] Example 4 is the same as Example 1, except that: multiple layers are prepared on the basis of Example 1, which may be greater than 3 layers, and hot pressing is performed, including three green sheets with different pore sizes with pore gradient, and reinforcing layers 2 are added between two green sheets, see Figure 5Example 4 uses green sheets with different pore sizes. The pore-forming agents of the green sheets can be polymethyl methacrylate microspheres with particle sizes of 50-80 μm, 20-40 μm, and 5-15 μm, respectively. The stretched titanium mesh 8 used in this example has a thickness of 50 μm and a porosity of 20%.
[0093] 1) The above-mentioned gradient porous transport layer with enhanced layer 2 is not necessarily prepared from hydrogenated dehydrogenated titanium powder, but can also be atomized titanium powder. In addition, in addition to titanium-based materials, iron, nickel, aluminum and their alloys can also be used as substrates to prepare the gradient porous transport layer with enhanced layer 2;
[0094] 2) The slurry 10 prepared by the gradient porous transmission layer component with the reinforcement layer 2 is configured as an alcohol-based solution, using anhydrous ethanol as a solvent; in addition, a water-based solution can be used, using water as a solvent;
[0095] 3) The stirring method in the preparation process of the gradient porous transport layer with the reinforcement layer 2 is magnetic stirring. In addition, other methods including but not limited to ball milling, blade stirrer, etc. can also be used for stirring the slurry 10;
[0096] 4) The pore-forming agent of the gradient porous transport layer with the reinforcement layer 2 is selected as polymethyl methacrylate microspheres. In addition, high molecular carbohydrate pore-forming agents including but not limited to starch, sucrose, cellulose, etc. can also be used for pore formation of the porous transport layer;
[0097] 5) The gradient porous transmission layer with the reinforcement layer 2 uses titanium fiber felt as the reinforcement layer 2 to increase the strength of the porous titanium sheet after sintering. In addition, a conductive porous layer made of a mesh or felt type including but not limited to titanium, nickel, aluminum, cobalt, carbon and other materials can also be used as the reinforcement layer 2 of the porous titanium sheet;
[0098] 6) The above-mentioned gradient porous transmission layer with enhanced layer 2 is a three-in-one structure, but a single-layer or multi-layer titanium sheet, that is, more than two layers, superimposed with enhanced layer 2 can also be used. This multi-in-one structure is within the protection scope of this patent.
[0099] In summary, the above-mentioned gradient porous transmission layer with a reinforcement layer 2 is Example 1 of the present invention, Example 2 is prepared by replacing the titanium fiber felt in Example 1 with a stretched titanium mesh, Example 3 is directly wet-formed, and a tungsten mesh is used as the reinforcement layer 2, Example 4 is prepared on the basis of Example 2 to form a multi-layer porous transmission layer (greater than 3 layers), Comparative Example 1 is a commercial titanium sheet, and Comparative Example 2 is a commercial titanium felt.
[0100] Figure 7It is the polarization curve of Examples 1-4 and Comparative Example 1 in the same PEM electrolyzer single cell. It can be seen from the figure that the performance of the gradient porous titanium sheet with reinforcement layer 2 is better than that of the commercial titanium sheet. Under the same current density, the gradient porous titanium sheet with reinforcement layer 2 has a lower voltage and higher efficiency. On the one hand, since the porous transmission layer prepared in the embodiment has gradient pores, its mass transfer capacity is better than that of the commercial titanium sheet; on the other hand, due to the addition of reinforcement layer 2, under the premise that the mechanical strength meets the requirements, the thickness of the gradient porous transmission layer can be greatly reduced compared with the commercial titanium sheet. The thickness of the gradient porous transmission layer prepared in the embodiment is about 400μm, while the thickness of the commercial titanium sheet is above 1000μm. The reduction in thickness can effectively reduce the ohmic resistance and improve the mass transfer capacity of the transmission layer. In addition, under large-scale commercial use, it can reduce the volume of the PEM electrolyzer stack and increase the hydrogen production rate per unit volume.
[0101] Figure 8 The high-frequency impedance comparison diagram of Example 1 and Comparative Example 2 in the same PEM electrolyzer single cell is shown in FIG. The smaller the high-frequency impedance, the smaller the ohmic resistance of the electrolyzer. It can be seen that Example 1 uses a pore-forming agent and uses a pore-forming agent with a smaller particle size at the contact surface between the porous transport layer and the catalyst layer 5, so its high-frequency impedance is lower than that of the titanium fiber felt. This is because the titanium fiber station is in line contact with the catalyst layer 5, and the contact surface resistance is large. The embodiment of the preferred pore-forming agent improves the contact with the catalyst layer 5, so it has a lower contact resistance, thereby reducing the ohmic resistance of the electrolyzer.
[0102] The preparation step parameters of Examples 2-4 are the same as those of Example 1. The differences are as follows: Example 2 is prepared by replacing the titanium fiber felt in Example 1 with a stretched titanium mesh, Example 3 is directly formed by a wet process, and a tungsten mesh is used as the reinforcement layer, and Example 4 is prepared by preparing a multi-layer porous transmission layer (greater than 3 layers) based on Example 2.
[0103] Additional note: The reinforcement layer itself does not account for the thickness of the final porous transmission layer, but is embedded between the titanium sheets to increase strength.
[0104] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that a technician familiar with the technical field can think of within the technical scope disclosed in the present invention should be covered within the protection scope of the present invention.
Claims
1. A porous transmission layer with a reinforced skeleton, characterized in that: The invention comprises a hole transport layer body arranged in a sandwich structure, wherein the hole transport layer body is composed of a first porous titanium sheet (1) at the top, a second porous titanium sheet (3) at the bottom, and a reinforcement layer (2) embedded between the first porous titanium sheet (1) and the second porous titanium sheet (3); and further comprises at least one group of cyclic additional layers; The circulating additional layer comprises a first porous titanium sheet (1) and a reinforcing layer (2) laminated to one side of the first porous titanium sheet (1), or the circulating additional layer comprises a second porous titanium sheet (3) and a reinforcing layer (2) laminated to one side of the second porous titanium sheet (3); The cyclic additional layer is overlapped with the hole transport layer body on one side or on both sides; The titanium sheet of the circulation additional layer and the reinforcement layer (2) can have the same porosity and pore size as the main body, or they can be different; the first porous titanium sheet (1) and the second porous titanium sheet (3) are both provided with pores; the thickness of the first porous titanium sheet (1) is the same as or different from the thickness of the second porous titanium sheet (3); the thickness of the first porous titanium sheet (1) and the thickness of the second porous titanium sheet (3) are both 1-2000 μm.
2. The porous transmission layer according to claim 1, characterized in that The reinforcement layer (2) is titanium fiber felt or titanium mesh (8) or tungsten mesh or nickel mesh.
3. The porous transmission layer according to claim 1, characterized in that The thickness of the reinforcement layer (2) is 1-2000 μm, and the porosity is 10%-90%.
4. The method for preparing a porous transport layer with a reinforced skeleton according to any one of claims 1 to 3, characterized in that: The preparation method of the hole transport layer body comprises the following steps: Step 1: Add solid and solvent into the same container; Step 2: The mixture prepared in step 1 is fully stirred by one or more of ball milling, homogenizer stirring or magnetic stirring, and the stirring time is 0.1-72h; Step 3: After the slurry (10) in step 2 is stirred, a plasticizer is added and stirred continuously, wherein the plasticizer is one or more of an alcohol plasticizer and an ester plasticizer; The alcohol plasticizer preferably includes one or more of polyethylene glycol, polyalkylene glycol and triethylene glycol; the ester plasticizer includes one or more of phthalate, diisodecyl phthalate and dipropylene glycol dibenzoate; the phthalate preferably includes one or more of butyl benzyl phthalate, diethylhexyl phthalate, diisononyl phthalate and dimethyl phthalate; Step 4: After the slurry (10) in step 3 is stirred, a degassing treatment is performed, wherein the degassing method includes one or more of vacuum degassing, vibration degassing and stirring degassing, so as to prevent bubbles generated by stirring from affecting subsequent processes; Step 5: subjecting the deaerated slurry (10) to wet forming; The basic steps of wet forming process are: Step 6: Drying the coated green sheet for 0.1-60 hours; and cutting the dried green sheet into the size required by the electrolytic cell; Step 7: hot-pressing the two cut green sheets with pores made by different pore-forming agents and the titanium fiber felt, with the titanium fiber felt sandwiched between the green sheets; Step 8: Degumming the green sheet after hot pressing to remove the residual binder, plasticizer and undried solvent in the green sheet. The degumming temperature is between 10-1000°C and the glue environment is vacuum and inert gas atmosphere. Step nine: The debonded green sheet is sintered at a high temperature, the sintering temperature is between 400-1800°C, and the sintering environment is a vacuum and inert gas atmosphere.
5. The preparation method according to claim 4, characterized in that: The solid reactants in step 1 include titanium powder, pore former and binder.
6. The preparation method according to claim 5, characterized in that: The titanium powder is hydrogenated dehydrogenated titanium powder with an average particle size of 1-500 μm, and the solvent is one or more of anhydrous ethanol, methyl ethyl ketone, trichloroethylene and water.
7. The preparation method according to claim 5, characterized in that: The binder is one or more of polyvinyl acetal, polyvinyl alcohol and polycarbonate acrylate.
8. The preparation method according to claim 5, characterized in that: The pore former is a high molecular organic material and / or a high molecular carbohydrate.
9. The preparation method according to claim 4, characterized in that: The high molecular organic material is polymethyl methacrylate and / or polystyrene.
10. The preparation method according to claim 4, characterized in that: High molecular carbohydrates are one or more of starch, sucrose and cellulose.
Citation Information
Patent Citations
Water transport plate with gradient distribution of apertures and preparation method thereof
CN106887597A
Preparation method of high-performance porous titanium flexible membrane for sewage treatment
CN112678921A
PEM water electrolysis cell anode porous diffusion layer and preparation method and application thereof
CN115090879A
Powder net composite gas diffusion layer and preparation method and application thereof
CN115478287A
Gradient pore and non-flow field diffusion layer for differential pressure type PEM electrolytic cell
CN117947437A